Midwifery Care Management of Intranatal Physiology in Mrs. "S" GIIIPIIA0 with 39 Weeks 2 Days Gestational Age at Haji Hospital Makassar - Vebrianti,; Taherong, Ferawati; Andryani, Zelna Yuni; Diarfah, Andi Dian (Jurnal Midwifery, 2025)
Introduction Normal childbirth is the process of delivering the fetus that occurs during pregnancy. The labor process is a complex stage as it involves saving two lives. A full-term pregnancy is defined as a gestational age of 37–42 weeks, with spontaneous delivery in a cephalic (head-first) presentation lasting approximately 18 hours, without any complications for either the mother or the baby. The purpose of this study is to provide physiological intranatal midwifery care to Mrs. “S”, GIII PII A0. Method used in this study is a case study approach following the 7 steps of Varney. Results of the case study on Mrs. “S”, a 31-year-old woman, showed that the normal labor care proceeded without any problems, indicating that the management provided was in accordance with normal delivery procedures during stages I–IV. The baby was born spontaneously/normally in good condition, and the mother's general condition was also good, with no complications during labor or postpartum. Conclusion, the care provided went smoothly and effectively, with no identified gaps. The midwife played a role in providing care in accordance with her competencies and authority.